Factors associated with diabetes concordant comorbidities among adult diabetic patients in Central Ethiopia: a cross-sectional study - Negussie, Yohannes Mekuria; Getahun, Mihiret Shawel; Bekele, Nardos Tilahun (Frontiers in Clinical Diabetes and Healthcare, 2023)
Background: Diabetes comorbidities are a serious public health issue that raises the risk of adverse health effects and complicates diabetes management. It also harms emotional health, medication adherence, self-management, and general quality of life. However, evidence is scarce in Ethiopia, particularly in the study area. Thus, this study aimed to estimate the prevalence of diabetes concordant comorbidities and identify factors associated with the presence of concordant comorbidities among adult diabetic patients in central Ethiopia.Methods: A health facility-based cross-sectional study was conducted among 398 adult diabetic patients. A computer-generated simple random sampling was used to select study participants.Data were collected using a structured data extraction checklist. The collected data were entered into Epi info version 7.2 and exported to SPSS version 27 for analysis. A binary logistic regression model was used to analyze the association between dependent and independent variables. An adjusted odds ratio with the corresponding 95% confidence interval was used to measure the strength of the association and statistical significance was declared at a p-value < 0.05.The prevalence of diabetes-concordant comorbidities was 41% (95% CI: 36.2-46.0). The multivariable logistic regression model showed that age 41-60 (AOR = 2.86, 95% CI: 1.60-5.13), place of residence (AOR = 2.22, 95% CI: 1.33-3.70), having type two diabetes (AOR = 3.30, 95% CI: 1.21-8.99), and having positive proteinuria (AOR = 2.64, 95% CI: 1.47-4.76) were significantly associated with diabetes concordant comorbidities.The prevalence of diabetes-concordant comorbidities was relatively high. Age, place of residence, type of diabetes, and positive proteinuria were factors associated with diabetesconcordant comorbidities. Prevention, early identification, and proper management of diabetes comorbidities are crucial.